Volume 2: 28th Design Automation Conference 2002
DOI: 10.1115/detc2002/dac-34091
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Experimental Design Applied to Ergonomics Testing Procedure

Abstract: Nonlinear constrained optimization algorithms are widely utilized in artifact design. Certain algorithms also lend themselves well to design of experiments (DOE). Adaptive design refers to experimental design where determining where to sample next is influenced by information from previous experiments. We present a constrained optimization algorithm known as superEGO (a variant of the EGO algorithm of Schonlau, Welch and Jones) that is able to create adaptive designs effectively. Its ability to allow easily fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Adapting the efficient metamodel-assisted strategies from the deterministic case to the noisy one is not a straightforward task, and several authors from different disciplines have proposed various solutions over the past decade (Forrester et al, 2006;Huang et al, 2006;Osborne et al, 2009;Picheny et al, 2012a;Srinivas et al, 2010;Scott et al, 2011;Sasena et al, 2002;Sakata et al, 2007). All these strategies basically share the same algorithmic principles and surrogate management framework; their differences mainly appear in the "infill sampling" criteria used for choosing new points sequentially.…”
Section: Introductionmentioning
confidence: 99%
“…Adapting the efficient metamodel-assisted strategies from the deterministic case to the noisy one is not a straightforward task, and several authors from different disciplines have proposed various solutions over the past decade (Forrester et al, 2006;Huang et al, 2006;Osborne et al, 2009;Picheny et al, 2012a;Srinivas et al, 2010;Scott et al, 2011;Sasena et al, 2002;Sakata et al, 2007). All these strategies basically share the same algorithmic principles and surrogate management framework; their differences mainly appear in the "infill sampling" criteria used for choosing new points sequentially.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 is a summary of the criteria reviewed in these surveys, with the search scope of each criteria defined as appropriate. I;, = aqi) r, = -&z) Sasena [2002a found that the most consistently well performing technique was the switching criterion (Switch in Table 1). For specific problems, other criteria might outperform this switching criterion, but only the switching criterion was consistently amongst the best.…”
Section: Larc E Data Setsmentioning
confidence: 99%
“…[Isaaks, 19891 In contrast, engineering metamodels (called Design and Analysis of Computer Experiments, DACE, Models) commonly employ a SCF similar to Equation 6. [Sasena, 2002a, andSasena, 2002bl where Bdefines the range of influence of the data (Or 0), and p defines the smoothness of the model (0 < p < 2) where increasing values of p lead to a smoother model. Both models interpolate given data points.…”
Section: Krlcing Metamodelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Sasena [2002a; found that the most consistently and best performing technique was the switching criterion (Switch in …”
Section: Hammersley Sequential Sampling (Hss)mentioning
confidence: 99%